The Position and Function of the Regional Representative Council in Constitutional System of Indonesia According to the Regional Autonomy Laws: A Shift from Legislative to Regional Executive - Suparto Suparto (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
This study aims to determine the position and function of the Regional Representative Council (DPRD) in the constitutional system of Indonesia. The study employed a normative legal approach and was analyzed qualitatively using secondary data. The finding revealed the position and function of the DPRD, an element of regional government administration, is currently regulated in one law, Law no. 23 of 2014 concerning Regional Government which previously regulated in the Law on the MPR, DPR, DPD, and DPRD. The DPRD has been regarded as a regional legislative council. In fact, a country adheres to the Unitary State concept do not familiar with regional legislatures. Even though, there is only one legislative council at the regional center, the DPR RI. In the previous law, Law no. 32/2004 states that DPRD has legislative, budgeting, and supervisory functions. The legislative function of the DPRD has resulted in ambiguity on the DPRD's position, a legislative council or part of the executive branch. This is because the function of legislative is to create laws owned by the legislative council. In this case, the DPR. Meanwhile, the DPRD only has the authority to formulate Perda. Based on Law no. 23 of 2014, the DPRD no longer has a legislative function. It is replaced by the function of forming a regional regulation. The DPRD which has been regarded as a regional legislative council, has begun to shift towards the regional executive